Evaluating Demand and Supply Side Factors for Client Refinance Intention and Microfinance Addiction in South Punjab - Gillani, Syeda Noor Zahra; Khan, Areeba; Adil, Muhammad (Pakistan Journal of Humanities and Social Sciences, 2025)
This study evaluates demand- and supply-side factors influencing client refinance intention and microfinance addiction in South Punjab by assessing financial, organizational, and macroeconomic variables that contribute to borrower dependency. The research applies GMM estimation to 309 observations, using dimension reduction techniques to identify significant variables affecting microfinance addiction. Data collection involved surveys, interviews, and scheduled visits to banks and client spaces, with analysis including short-run and long-run estimations that control for firm structure, loan characteristics, liquidity, debt-to-equity ratio, and macroeconomic factors. Higher loan size, percentage of women borrowers, liquidity, and firm size positively impact microfinance addiction, while active borrower numbers, cost per borrower, and debt-to-equity ratio negatively influence addiction. GDP exhibits a negative relationship, indicating economic stability reduces microfinance dependence. These results provide policy insights for MFIs to regulate lending practices and prevent over-indebtedness. Financial literacy programs and improved borrower monitoring can mitigate excessive refinancing, while policymakers should implement borrower segmentation strategies to promote sustainable financial inclusion while reducing addiction risks.